Fabrication, Characterization, and Optimization of CdS and CdSe Quantum Dot-Sensitized Solar Cells with Quantum Dots Prepared by Successive Ionic Layer Adsorption and Reaction - H. K. Jun; M. A. Careem; A. K. Arof (International Journal of Photoenergy)
CdS and CdSe quantum dot-sensitized solar cells (QDSSCs) were used for the study of determining the optimum preparation parameters that could yield the best solar cell performance. The quantum dots (QDs) were coated on the surface of mesoporous TiO2 layer deposited on FTO substrate using the successive ionic layer adsorption and reaction (SILAR) method. In this method the QDs are allowed to grow on TiO2 by dipping the TiO2 electrode successively in two different solutions for predetermined times. This method allows the fabrication of QDs in a facile way. Three preparation parameters that control the QD fabrication were investigated: concentration of precursor solutions, number of dipping cycles (SILAR cycles), and dipping time in each solution. CdS based QDSSC showed optimum performance when the QDs were prepared from precursor solutions having the concentration of 0.10 M using 4 dipping cycles with the dipping time of 5 minutes in each solution. For CdSe QDSSC, the optimum performance was achieved with QDs prepared from 0.03 M precursor solutions using 7 dipping cycles with 30 s dipping time in each solution. The QDs deposited on TiO2 surface were characterized using UV-vis absorption spectroscopy, FESEM, and TEM imaging.